SEM-EDXA of CCA-treated Rubberwood (Hevea brasiliensis) - Jusoh, Ismail; Kamdem, D. Pascal (40th Annual Meeting, Beijing, China, 2009)
The microdistribution of chromated copper arsenate (CCA) preservative in rubberwood was studied using scanning electron microscope in conjunction with energy dispersive X-ray analyzer (SEM-EDXA). Bulk X-ray analysis showed that there was a high accumulation of chromium, copper, and arsenic in the vessels and lower concentration of the three preservative elements in fibres. Chromium appeared to record the highest while copper the lowest X-ray intensity in all cells. SEM-EDXA of semi-thin sections demonstrated that X-ray intensities of Cr, Cu, and As were concentrated in the fibre-to-vessel cell corner (FVcc) and fibre-to-vessel middle lamella (FVMlJ while the lowest intensity was recorded in S2 layer of fibre. Linescan analyses illustrated that higher count rates of chromium, copper, and arsenic were found in the middle lamella compared to the fibre S2 layer in CCA-treated rubberwood. The increase of the solution strength in chromium, copper, and arsenic corresponds to an increase in Cr, Cu, and As level in wood cells.